2006
DOI: 10.1038/sj.ki.5000241
|View full text |Cite
|
Sign up to set email alerts
|

A novel missense mutation of SLC7A9 frequent in Japanese cystinuria cases affecting the C-terminus of the transporter

Abstract: Cystinuria is caused by the inherited defect of apical membrane transport systems for cystine and dibasic amino acids in renal proximal tubules. Mutations in either SLC7A9 or SLC3A1 gene result in cystinuria. The mutations of SLC7A9 gene have been identified mainly from Italian, Libyan Jewish, North American, and Spanish patients. In the present study, we have analyzed cystinuria cases from oriental population (mostly Japanese). Mutation analyses of SLC7A9 and SLC3A1 genes were performed on 41 cystinuria patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 30 publications
0
28
1
Order By: Relevance
“…Tanaka et al 4 reported a 45-year-old man with recurrent renal stones who developed ataxia and extrapyramidal signs, suggesting both cerebellar and basal ganglia involvement. Unlike these cases, our case had no urinary stones, probably because of the milder phenotype associated with the heterozygous (not homozygous) mutation in the SLC7A9 gene, and no SLC3A1 gene abnormality 1. In fact, the present case had a lower urinary cystine concentration than the Japanese cases.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Tanaka et al 4 reported a 45-year-old man with recurrent renal stones who developed ataxia and extrapyramidal signs, suggesting both cerebellar and basal ganglia involvement. Unlike these cases, our case had no urinary stones, probably because of the milder phenotype associated with the heterozygous (not homozygous) mutation in the SLC7A9 gene, and no SLC3A1 gene abnormality 1. In fact, the present case had a lower urinary cystine concentration than the Japanese cases.…”
Section: Discussioncontrasting
confidence: 56%
“…Lee et al 2 reported a 13-year-old Korean boy with cystinuria with a heterozygous G173R mutation in the SLC7A9 gene, who had intellectual disability and sensory ataxia from posterior column impairment, but no renal stones. Shigeta et al 1 reported that 35 out of 41 patients with cystinuria in Japan had a cystinuria-specific heterozygous and/or homozygous mutation of SLC7A9 with no other polymorphic gene abnormality. Also, there were 25 cases with the P482L homozygous mutation in SLC7A9 and six cases had heterozygous P482L mutations, as in this case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cohorts of patients from Europe, Asia, and North America have been genotyped (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) along with a recently published group of United Kingdom patients (22).…”
Section: Introductionmentioning
confidence: 99%
“…23,24,27 Several explanations have been pro posed to account for these patients with no known muta tion; for example, mutations leading to cystinuria might be in unexplored regions of SLC3A1 and SLC7A9, or mutations in a third, as yet uncharacterized gene might lead to cystinuria. 6 Furthermore, hypomorphic poly morphisms in c ombination with a mutated allele might have a role in cystinuria.…”
Section: Key Pointsmentioning
confidence: 98%